Synergistic enhancement of electrochemical alcohol oxidation by combining NiV-layered double hydroxide with an aminoxyl radical - Suiqin Li; Shibin Wang; Yuhang Wang; Jiahui He; Kai Li; James B. Gerken; Shannon S. Stahl; Xing Zhong; Jianguo Wang (Nature Communications)
Abstract Electrochemical alcohol oxidation (EAO) represents an effective method for the production of high-value carbonyl products. However, its industrial viability is hindered by suboptimal efficiency stemming from low reaction rates. Here, we present a synergistic electrocatalysis approach that integrates an active electrode and aminoxyl radical to enhance the performance of EAO. The optimal aminoxyl radical (4-acetamido-2,2,6,6-tetramethylpiperidine 1-oxyl) and Ni0.67V0.33-layered double hydroxide (LDH) are screen as cooperative electrocatalysts by integrating theoretical predictions and experiments. The Ni0.67V0.33-LDH facilitates the adsorption and activation of N-(1-hydroxy-2,2,6,6-tetramethylpiperidin-4-yl)acetamide (ACTH) via interactions with ketonic oxygen, thereby improving selectivity and yield at high current densities. The electrolysis process is scaled up to produce 200 g of the steroid carbonyl product 8b (19-Aldoandrostenedione), achieving a yield of 91% and a productivity of 243 g h-1. These results represent a promising method for accelerating electron transfer to enhance alcohol oxidation, highlighting its potential for practical electrosynthesis applications.